Development of Numerous Nerve Fibers in the Epidermis of Hairless Mice With Atopic Dermatitis-Like Pruritic Skin Inflammation - Masanori Fujii; Keisuke Akita; Nobuaki Mizutani; Takeshi Nabe; Shigekatsu Kohno (Elsevier, 2007)
Itching is the most important symptom in atopic dermatitis because the persistent scratching in response to itching aggravates the disease. However, the etiologic mechanisms of itching in atopic dermatitis remain uncertain. HR-1 hairless mice fed a special diet, HR-AD, develop atopic dermatitis-like symptoms with prolonged scratching episodes. The purpose of this study was to examine whether skin nerve fiber changes were involved in the prolonged scratching seen in this mouse model. On day 56 after the start of feeding, prolonged scratching, as well as atopic dermatitis-like skin changes, were clearly observed in HR-AD-fed mice, while no abnormal changes were observed in mice fed a normal diet. Immunohistochemical analyses of the skin using antibody to protein gene product 9.5 showed the development of numerous immunoreactive nerve fibers in the epidermis of HR-AD-fed mice. Furthermore, after cessation of HR-AD feeding, the reduction in intraepidermal nerve fibers coincided with decreased scratching. Neither the prolongation of scratching nor the increase in intraepidermal nerve fibers was affected by dexamethasone treatment. Thus, the increased number of intraepidermal nerve fibers could be involved in the aggravation of itch-related scratching observed in this model. Keywords:: itch, atopic dermatitis, nerve fiber, hairless mice, protein gene product 9.5